Modelling the spatial crosstalk between two biochemical signals explains wood formation dynamics and tree-ring structure. (28th November 2020) - Hartmann, Félix P; Rathgeber, Cyrille B K; Badel, Éric; Fournier, Meriem; Moulia, Bruno
Abstract : A dynamic model indicates that two interacting signals (auxin, plus a cytokinin or the TDIF peptide) can drive wood formation dynamics and tree-ring structure development in conifers. Abstract: In conifers, xylogenesis during a growing season produces a very characteristic tree-ring structure: large, thin-walled earlywood cells followed by narrow, thick-walled latewood cells. Although many factors influence the dynamics of differentiation and the final dimensions of xylem cells, the associated patterns of variation remain very stable from one year to the next. While radial growth is characterized by an S-shaped curve, the widths of xylem differentiation zones exhibit characteristic skewed bell-shaped curves. These elements suggest a strong internal control of xylogenesis. It has long been hypothesized that much of this regulation relies on a morphogenetic gradient of auxin. However, recent modelling studies have shown that while this hypothesis could account for the dynamics of stem radial growth and the zonation of the developing xylem, it failed to reproduce the characteristic tree-ring structure. Here, we investigated the hypothesis of regulation by a crosstalk between auxin and a second biochemical signal, by using computational morphodynamics. We found that, in conifers, such a crosstalk is sufficient to simulate the characteristic features of wood formation dynamics, as well as the resulting tree-ring structure. In this model, auxin controls cell enlargement rates while another signal (e.g. cytokinin, tracheary element differentiation inhibitory factor) drives cell division and auxin polar transport.